(untitled) - Morrissey, John F. (Sudbury, Mass., 2009)
The new Ninth Edition of Introduction to the Biology of Marine Life has been revised to include coverage of recent advances in research and technology, as well as current trends and problems within the field of marine biology. Maintaining the student-friendly style of the previous edition, the Ninth Edition now includes information on marine viruses, marine fungi, estimating productivity from satellite images, problems faced by coral reefs, and much more. The authors have incorporated a completely update art package to enhance comprehension and reinforce key concepts; and new Research in Progress boxes have been included to encourage students to participate in the learning process. With its updated content, thorough coverage, and accessible teaching style, Introduction to the Biology of Marine Life is a user-friendly guide to marine biology for the non-major.
Keywords: Marine biology